ANALISIS DAMPAK EKONOMI PADA MASA PANDEMI COVID-19 TERHADAP UMKM DI WILAYAH KOTA PEKANBARU (Studi Kasus Kecamatan Payung Sekaki) - Hidayat Fajri Nurul; Setiawan Deny; Pailis Armas Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the impact of the pre and ongoing Covid-19 pandemic on the business profits of MSMEs in the city of Pekanbaru. The method used in this study is a comparative descriptive and quantitative method. The population in this study were MSME actors in Payung Sekaki District, Pekanbaru City and registered at the Pekanbaru City Cooperative and UMKM Service, totaling 14,563 units of UMKM players in Pekanbaru City and 6,155 units of UMKM players in Payung Sekaki District. In this study, researchers used simple random sampling. From the above calculations, it can be seen that the number of samples to be studied is as many as 98 respondents. The data in this study were analyzed by Different Test or Paired T-test. The results of this study indicate that the impact prior to the Covid-19 Pandemic Period on the capital of MSMEs in the Pekanbaru City Area was Rp. 10,000,000– Rp. 19,999,999 and during the Covid-19 Pandemic Period the capital was <Rp. 10,000,000. The impact before the Covid-19 Pandemic Period on the turnover of MSMEs in the City of Pekanbaru was Rp. 10,000,000 - Rp. 19,999,999 and during the Covid-19 Pandemic Period, the turnover was Rp. 10,000,000. The impact prior to the Covid-19 Pandemic Period on the benefits of MSMEs in the Pekanbaru City Area of Rp. 10,000,000 - Rp. 19,999,999 and during the Covid-19 Pandemic Period, a profit of Rp. 10,000,000.Keywords: The Covid-19 Pandemic, Economy